68Ga labeled Erlotinib: A novel PET probe for imaging EGFR over-expressing tumors. Issue 19 (1st October 2017) - Jain, Akanksha; Kameswaran, Mythili; Pandey, Usha; Prabhash, Kumar; Sarma, Haladhar Dev; Dash, Ashutosh
Graphical abstract: Highlights: Alkyne group of Erlotinib modified by CuAAC reaction for conjugation with NOTA. NOTA-Erlotinib radiolabeled with 68 Ga in 95 ± 2% yields. 68 Ga-NOTA-Erlotinib showed 9.8 ± 0.4% uptake in A431 cells. Inhibition of up to 55.1 ± 0.2% on addition of 10 µg Erlotinib in A431 cells. Moderate tumor accumulation in EGFR + SCID mice (1.53 ± 0.11% ID/g at 30 min p.i). Abstract: Molecular imaging using radiolabeled Tyrosine Kinase Inhibitors (TKI) is a promising strategy for detection and staging of EGFR-positive cancers. A novel analogue of one such TKI, Erlotinib has been developed for PET imaging by derivatizing the parent Erlotinib molecule for conjugation with the bifunctional chelator p -SCN-Bn-NOTA towards radiolabeling with 68 Ga. NOTA-Erlotinib conjugate was synthesized and characterized by NMR and ESI-MS techniques. The conjugate was radiolabeled with 68 Ga in 95 ± 2% yield, as evidenced by HPLC characterization. The log P value of 68 Ga-NOTA-Erlotinib was – (0.6 ± 0.1). The 68 Ga-NOTA-Erlotinib conjugate was characterized using its nat Ga-NOTA-Erlotinib surrogate. Cell viability studies showed that the NOTA-Erlotinib conjugate retained the biological efficacy of the parent Erlotinib molecule. Further, 68 Ga-NOTA-Erlotinib exhibited an uptake of 9.8 ± 0.4% in A431 cells which was inhibited by 55.1 ± 0.2% on addition of cold Erlotinib (10 µg) confirming the specificity of the radioconjugate for EGFR expressing cells. In the biodistribution studies carried out in tumor bearing SCID mice, 68 Ga-NOTA-Erlotinib conjugate showed moderate tumor accumulation (1.5 ± 0.1% ID/g at 30 min p.i.; 0.7 ± 0.2% ID/g at 1 h p.i.). Hepatobiliary clearance of the radioconjugate was observed. The 68 Ga-NOTA-Erlotinib conjugate was found to have high in vivo stability as determined by the metabolite analysis study using urine sample of the Swiss mice injected with the preparation. The overall properties of 68 Ga-NOTA-Erlotinib are promising and merit further exploration. To the best of our knowledge, this is the first report on the design of a 68 Ga labeled Erlotinib for PET imaging of EGFR and opens avenues for the successful development of 68 Ga labeled TKI for imaging of EGFR over-expressing tumors.